Differences in career longevity before and after implementation of the Women's Tennis Association Tour Age Eligibility Rule and Player Development Programmes: a 25-year study - Carol L Otis; Brian Hainline; Chris Harwood; Neeru A Jayanthi; Rick Jensen; Ashley Keber; Emily Kroshus; Thomas Livengood; Kathleen Stroia; Ann Quinn; Sarka Vitkova; Stephanie A Kliethermes (2022)
Objectives: To assess differences in career longevity, as a potential marker of athlete well-being, before and after the 1995 implementation of the Women's Tennis Association (WTA) Age Eligibility Rule (AER) and Player Development Programmes (PDP), which focused on organisational, physical and psychosocial education, skill building and support for adolescent athletes (≤17 years).  Methods: Career longevity data were collected through 2019 on adolescent players who began professional tournament play between 1970 and 2014 and reached a WTA singles ranking of 1-150 for a minimum of 1 week during their careers. Players were separated into pre-AER/PDP and post-AER/PDP groups, consisting of those who played their first professional events (FPE) before or after 1 January 1995. Measures of career longevity included career duration and premature retirement. Results Eight-hundred and eleven players were included in this study (51% pre-AER/PDP). The median career duration was 14.2 years for the post-AER/PDP group compared with 12.1 years for the pre-AER/PDP group (p